PENGARUH INISIASI MENYUSU DINI (IMD) TERHADAP PERUBAHAN SUHU TUBUH PADA BAYI BARU LAHIR DI TPMB NY LIALUT KEC. BULULAWANG KAB. MALANG - Purwati, Anik; Fidha FW, Indy (NHM PRESS, 2024)
At the beginning of the baby's birth, namely in the first half hour, his body temperature can drop around 3-4°C, besides that the calories in the baby's body will also experience a shrinkage of 4 x adult calories. At room temperature 20-25°C, the baby's temperature drops around 0.3°C every minute. A very drastic decrease in body temperature or what is called hypothermia in newborns can affect metabolic and physiological processes in babies, in addition to affecting the respiratory rate, the pulse rate slows down, low blood pressure and consciousness can also be reduced or even lost, It can result in death. Objective: The purpose of this study is to determine the effect of Early Breastfeeding Initiation (IMD) on changes in body temperature in newborns. Methods: This type of research is quantitative with design This type of research is Pre-experimental with a one-group Pretest-Posttest Design approach (Siyoto, 2015).The sampling technique with non-probability sampling is purposive sampling. Data were obtained using SPO sheets and observation sheets. The data were analyzed using univariate and bivariate analysis using the Paired T-Test. The mandatory output of this study is the publication of a journal and an additional output of making a booklet on Early Breastfeeding Initiation (IMD). Results: The effect of Early Initiation of Breastfeeding (IMD) on changes in body temperature of newborns was obtained with p value = .003 < α = 0.05. ). Conclusion: The conclusion that H1 is accepted means that there is an Effect of Early Breastfeeding Initiation (IMD) on Changes in Newborn Body Temperature at TPMB Ny Lialut Kec.Bululawang Kab. Malang .The implication is that with the initiation of early breastfeeding (IMD) it can maintain body temperature in newborns can also help babies in getting breast milk earlier after birth.